Applying Contextual Teaching Strategies to Boost Learning Interest in Religious Education at SMP Muhammadiyah Mayangan, Probolinggo - Afifi, Ahmad Fuad; Andriana, Andriana (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2024)
The Contextual Teaching and Learning (CTL) approach integrates academic material with students’ real-world experiences, encouraging them to apply their knowledge in daily life. CTL fosters natural learning through active student participation in projects rather than traditional teacher-centered instruction. This approach emphasizes students as active learners, enhancing their engagement and understanding. Learning interest, defined as a stable tendency to engage with specific activities, plays a vital role in shaping students’ academic attitudes. Educators play a crucial role in nurturing this interest. This study explores three key aspects of CTL in Islamic religious education at Muhammadiyah Mayangan Middle School, Probolinggo: planning, implementation, and evaluation. Data was gathered through field research methods, including interviews, observations, and documentation, supported by primary and secondary sources. Findings reveal that lesson planning incorporates CTL strategies to create structured and engaging lessons. The implementation of CTL includes seven components: constructivism, questioning, discovery, modeling, learning communities, reflection, and authentic assessment, all aimed at fostering meaningful learning experiences. Evaluation methods extend beyond written tests to include active classroom participation, such as expressing opinions, answering questions, and participating in quizzes. The results highlight the effectiveness of CTL strategies in increasing student interest and engagement in Islamic religious education.